161k views
2 votes
5-2(4a+1)+3a=13

A= 2/3
A= -2
A= -6/5
A=2

User Fresko
by
4.6k points

2 Answers

1 vote

Answer:

b

Explanation:

User Mtekeli
by
4.7k points
5 votes

Answer:

a = -2

Simplifying 5 + -2(4a + 1) + 3a = 13 Reorder the terms: 5 + -2(1 + 4a) + 3a = 13 5 + (1 * -2 + 4a * -2) + 3a = 13 5 + (-2 + -8a) + 3a = 13 Combine like terms: 5 + -2 = 3 3 + -8a + 3a = 13 Combine like terms: -8a + 3a = -5a 3 + -5a = 13 Solving 3 + -5a = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5a = 13 + -3 Combine like terms: 3 + -3 = 0 0 + -5a = 13 + -3 -5a = 13 + -3 Combine like terms: 13 + -3 = 10 -5a = 10 Divide each side by '-5'. a = -2

User Indichimp
by
4.7k points